Recent developments in the Canadian economy: Spring 2025 - Guy Gellatly; Carter McCormack (Economic and Social Reports)
This article provides an integrated summary of recent economic developments, highlighting changes in the economic data during late 2024 and early 2025. The article focuses on how economic conditions have changed as households and businesses adjust to ongoing uncertainty over Canada's trading relationship with the United States.